Ultrasonographic guided Fine Needle Aspiration Cytology (FNAC) in the Diagnosis of Intra-abdominal Solid Mass in Children (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Ultrasound guided needle biopsy is rapidly growing and important diagnostic technique in radiology practices throughout the world. It has become an accurate, safe and widely accepted technique for confirmation of suspected malignant masses and characterization of many benign lesions in various intraabdominal locations. It also decreases patient costs by obtaining the need for an operation, decreasing the duration of hospital stay, and decreasing the number of examinations necessary during a diagnostic evaluation. Objectives of the study: To establish ultrasound guided FNAC as an accurate method of diagnosis of intraabdominal solid mass and to find out the correlation between FNAC with histological findings. Material and Methods: This was a prospective comparative study. The study has been carried out in the department of pediatric Surgery Sher-e-Bangla Medical College Hospital, Barisal and Radiology & Imaging Department, SBMCH. This study was conducted from November 2022 to January 2024 (15 months). Forty five cases, all undergone both FNAC and open biopsy. Among them 24 cases were male; 21 were females. Age ranges from 3 months to 14 years. Data, collected on predesigned data collection sheet for each individual case was compiled on a master chart from which data were analyzed using a computer based software, Statistical Package for Social Science (SPSS) to arrive at definitive conclusion in respect to objective of this study. Prior to the commencement of this study, the thesis protocol was approved by the Thesis Committee, SBMCH. Result: Out of 45 cases cytological diagnosis, 10 cases were found to be benign. Among them 4 cases nonneoplastic and 6 neoplastic (benign) and 33 malignant; 01 was found suspicious of malignancy and 01 was unsatisfactory for cytological examination. Comparison of cytological with histological diagnosis of all patients, 9 cases were benign and 36 cases were malignant. In the final histopathological diagnosis shows that out of 10 benign lesions diagnosed cytologically, 01 case was found malignant histologically(i.e. False negative 01).33 malignant cases were diagnosed cytologically, all were confirmed histologically(i.e.no false positive). 01 suspicious case was reported cytologically, but found malignant histologically. 01 unsatisfactory case was proved malignant histologically. Conclusion: Ultrasound imaging can easily and precisely visualize the intra-abdominal mass lesion and sonography aided fine needle aspiration cytology can be regarded as the investigation of choice for early confirmation and exclusion of neoplastic diseases in cases presenting with intra-abdominal masses. It allows morphological evaluation of all doubtful lesions without time consuming and costly surgery, but without impairing the diagnostic reliability.Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):33-39